The Ethnic Minorities in Three Daily Papers ("Lietuvos Aidas", "Lietuvos Rytas", "Respublika") - Beresnevičiūtė, Vida; Nausėdienė, Inga (Sociologija. Mintis ir veiksmas, 1999)
The paper analyzes the presentation of the issue of ethnic minorities in the daily papers „Lietuvos aidas“, „Lietuvos rytas“ and „Respublika“. Its concerns are connected with the questions of the relation between ethnic groups, the processes of formation of stereotypes and the relation between the societal self-consiousness and the social reality. The authors view the daily papers as a sites of symbolic power and develop their argument by analysing the problem of representation. The issue of concern here is the readers’ trust in the press and the mass media. Authors note that the existence stereotypes is innevitable because they are grounded in the everyday practices. Yet the problem is the social reification of the images that are the result of the process of generalizing particularity (V.N. Parrillo, J.R.Feagin).